“I want to speak like a native speaker”: Exploring Learners’ Motivational Factors After the English Camp - Reza Anggriyashati Adara; Raden Hengki Rahmanto (Journal of English Language Studies, 2025)
This study investigated the impact of an English camp on the motivational factors of English as a Foreign Language (EFL) learners. Thirty high school students participated in an eight-day English camp, and pre- and post-camp questionnaires adapted from Taguchi et al. (2009) were used to measure changes in motivation. The key constructs examined included criterion measures, the ideal L2 self, the ought-to L2 self, family influence, instrumentality, attitudes toward learning English, linguistic confidence, and learning interest. Results showed increases in linguistic confidence (from M = 3.50 to 3.83), the ideal L2 self, and the ought-to L2 self (both from M = 3.27 to 3.50), suggesting that the camp experience helped students develop stronger self-perceptions as English users. Meanwhile, slight decreases in criterion measures (3.69 to 3.58), instrumentality (3.63 to 3.54), and learning interest (3.50 to 3.17) may indicate a shift away from external motivators and highlight the need for more engaging and practically relevant activities. These findings suggest that future English camps should prioritize building students' ideal L2 selves through personalized goal-setting and confidence-building tasks, while also incorporating exposure to professionals who use English in real-world contexts (e.g., pilots, engineers, or flight attendants) to strengthen practical motivation. Additionally, camp activities should include diverse, student-centered formats to sustain engagement and prevent motivational fatigue. More broadly, EFL teaching practices can benefit from adopting similar strategies—fostering learners’ linguistic confidence and internal motivation through authentic, meaningful language use beyond test preparation.